Kepemimpinan Kepala Sekolah dalam Pembentukan Karakter Islami Peserta didik - Fauziyyah Nur Azmi Nst; Iin Kurniati; El-Mubarak Rijal Agung Wibawa (Universitas Muhammadiyah Enrekang, 2021)
Education in general with national education has the same function and purpose in shaping good character / personality for students. This shows how serious the government is in realizing character education in this beloved country. Building character is not an instant job and by one institution alone. A person's character is formed as the cumulative impact of lessons learned from the journey of learning and working throughout one's life involving various institutions, both formal, informal, and non-formal education where a person finds himself from infancy to adulthood through proper education (Joni, 2008). In the world of education, the principal plays an important role in shaping the character of students. Because decisions will be made based on orders from the principal. This research uses the library research method because it makes it easier for us to get information, and this information can be obtained from scientific books, research reports, scientific essays, theses and dissertations, regulations, provisions, yearbooks, encyclopedias and other sources. other written and electronic sources.